Frequency regulation strategy of direct drive permanent magnet synchronous wind power generation system based on RPC principle - Zhang, Xiaoke; Xia, Dawei; Zhang, Hengyou; Wang, Jinggang (Frontiers in Energy Research, 2023)
The continuous integration of renewable energy into the grid has reduced its inertia and damping levels. When disturbances occur, the grid is prone to frequency excursion issues, which restrict the further utilization of renewable energy. Consequently, an increasing number of grid codes require active participation of renewable energy sources in the system’s frequency regulation (FR). Direct-drive permanent magnet synchronous wind power systems, characterized by their simple structure and high reliability, have gradually become the mainstream in wind power systems. By controlling the pitch angle to reserve surplus power, the wind turbines can actively engage in frequency regulation during disturbances. However, due to limited power reserve capacity, traditional FR methods struggle with parameters tuning, thus failing to achieve the desired effect. To this end, this paper proposes an FR strategy for direct-drive permanent magnet synchronous wind power systems based on the principle of rapid power compensation (RPC). It circumvents the challenges associated with parameter tuning, and achieves optimal FR performance for wind turbine inverter under power-limited conditions. Firstly, it is demonstrated that the proposed RPC control, when making full use of power reserves, can achieve FR effects equivalent to optimal PD control through rigorous mathematical analysis. Subsequently, the RPC control is divided into four operating modes to address FR requirements under different conditions. The transitions between these modes are explained, and the detailed implementation of the RPC control is provided. Finally, the effectiveness and superiority of the proposed control strategy are validated through simulation based on Matlab/Simulink.